Building an ultrafast fiber laser - Neo, Bo Sheng (Nanyang Technological University, 2024)
Fibre lasers have several qualities which make them attractive for ultrashort pulse generation in the femtosecond region. Their setups can be built with relatively low cost and can be very compact and rugged—particularly if no free-space optics are used. Moreover, the laser output is delivered naturally to an optical fibre, making them highly versatile in various applications. In this project, a blue light fibre laser machine generating high power femtosecond pulses is to be built by utilising the Up-Conversion process and Mamyshev Oscillator. In this project further analysis of Up-Conversion process has been taken and produced valuable outcomes. The significances of the results have proven the possibility of Up-Conversion in Thulium-Doped Fluoride Fibre. The presence of stimulated emission is observed in the output has demonstrate a proof of concept for this process. By building this high-power ultrafast blue light fibre laser machine, the work done will contribute tremendously towards telecommunication, industrial usage, and research field, thereby highlighting its potential in advancing ultrafast fibre laser technology.